The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1242/jcs.169391
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-1 promotes post-Golgi trafficking of NCAM140 and NCAM180 to the cell surface

Abstract: The neural cell adhesion molecule (NCAM, also known as NCAM1) is important during neural development, because it contributes to neurite outgrowth in response to its ligands at the cell surface. In the adult brain, NCAM is involved in regulating synaptic plasticity. The molecular mechanisms underlying delivery of NCAM to the neuronal cell surface remain poorly understood. We used a protein macroarray and identified the kinesin light chain 1 (KLC1), a component of the kinesin-1 motor protein, as a binding partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 81 publications
(113 reference statements)
1
14
0
Order By: Relevance
“…Disruption of the interaction between NCAM and KLC1 or KLC1 knockdown using targeted siRNA in CHO cells and mouse cortical neurons results in reduced delivery of NCAM to the cell surface and accumulation of NCAM in the Golgi apparatus. 23 These observations are in agreement with studies in Drosophila showing that the transport and localization of Fasciclin II, an ortholog of NCAM in flies, is affected in kinesin light chain (Klc) mutant larvae, and in larvae with mutated unc-51, a kinase which genetically interacts with Klc in kinesin-mediated axonal transport. 29 The binding site for KLC1 has been mapped to amino acids 748-755 (CGKAGPGA), a region which overlaps with the region previously reported to be important for the sorting of NCAM in MDCK cells.…”
Section: Molecular Mechanisms Of the Intracellular Transport Of Ncam supporting
confidence: 90%
See 3 more Smart Citations
“…Disruption of the interaction between NCAM and KLC1 or KLC1 knockdown using targeted siRNA in CHO cells and mouse cortical neurons results in reduced delivery of NCAM to the cell surface and accumulation of NCAM in the Golgi apparatus. 23 These observations are in agreement with studies in Drosophila showing that the transport and localization of Fasciclin II, an ortholog of NCAM in flies, is affected in kinesin light chain (Klc) mutant larvae, and in larvae with mutated unc-51, a kinase which genetically interacts with Klc in kinesin-mediated axonal transport. 29 The binding site for KLC1 has been mapped to amino acids 748-755 (CGKAGPGA), a region which overlaps with the region previously reported to be important for the sorting of NCAM in MDCK cells.…”
Section: Molecular Mechanisms Of the Intracellular Transport Of Ncam supporting
confidence: 90%
“…21 Experiments with various truncated forms of NCAM indicate that the intracellular domain of NCAM is not required for the delivery of NCAM to the cell surface in various cell types including neurons. 22,23 This observation is probably not surprising since the GPI-anchored NCAM120 is efficiently delivered to the cell surface of neurons. 24 The intracellular domain of NCAM is however exposed for interactions with proteins in the cytosol, suggesting that it may play a regulatory role.…”
Section: Molecular Mechanisms Of the Intracellular Transport Of Ncam mentioning
confidence: 91%
See 2 more Smart Citations
“…In this study, we show that KLC1 interacts with WAVE1, (BNIP-2), and protein interacting with APP tail 1 (PAT1) [1,8,10,14,21,22]. In this study, we have identified that WAVE1 interacted with the TPR domain of KLC1.…”
Section: Discussionmentioning
confidence: 71%